2020
DOI: 10.1039/c9fo02180a
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and cookie-making performance of oleogels prepared with crude and refined soybean oil: a comparative study

Abstract: The objective of this research was to fabricate crude soybean oil oleogels (CSO) using β-sitosterol (BS) and/or monoacylglycerol (MAG) and compare their role with that of refined soybean oil oleogels (RSO) in cookie making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Consequently, the replacement of shortening with CBW-O positively contributed to the physical properties of cookies. Moreover, as shown in the study of Zhao et al [ 45 ], it can be concluded that the hardness of oleogel is not directly correlated to the hardness of cookies.…”
Section: Resultsmentioning
confidence: 93%
“…Consequently, the replacement of shortening with CBW-O positively contributed to the physical properties of cookies. Moreover, as shown in the study of Zhao et al [ 45 ], it can be concluded that the hardness of oleogel is not directly correlated to the hardness of cookies.…”
Section: Resultsmentioning
confidence: 93%
“…Li & Liu, 2019;Wang et al, 2021;Woern et al, 2021). Conversely, oleogel-based products exhibiting simi-lar or improved properties to those of control products have been reported in formulations with relatively low-fat content (∼11-20 wt%) and when the substitution was accompanied by changes in recipe formulas (Alejandre et al, 2019;Barbut et al, 2019;Giacomozzi et al, 2018;Palla et al, 2020;Zhao et al, 2020). The results of these studies suggest that it would be beneficial to approach oleogel design from a broader perspective, considering the oleogel as a component of a more complex food matrix with its potential interactions.…”
Section: Food Applications Of Mg Oleogelsmentioning
confidence: 99%
“…In fact, their use in different food systems has become the subject of much recent investigation. The potential of SMG oleogels as an ingredient to reduce saturated fats and eliminate trans fats by full or partial solid fat replacement has been studied in different food items, such as cakes, cookies, muffins, sweet bread, filling cream, margarine, chocolate spread, dark chocolate, and bologna sausage (Calligaris et al., 2013; Fayaz et al., 2017; Ferro et al., 2021; Giacomozzi et al., 2018; L. Li & Liu, 2019; Mohanan et al., 2020; Palla et al., 2020; Wang et al., 2021; Zhao et al., 2020). Moreover, oleogels formulated with MGs and additional gelators (e.g., EC, PS, and CW) have been tested in the elaboration of margarine, shortening, puff pastry, tart pastry, and meat‐based products (Alejandre et al., 2019; Barbut et al., 2019; Calligaris et al., 2021; Rodríguez‐Hernández et al., 2021; Sim et al., 2021; Woern et al., 2021).…”
Section: Food Applications Of Mg Oleogelsmentioning
confidence: 99%
“…Among the oleogelators, rice bran wax (RBW) is an effective thermoreversible oleogelator that can structure oil at concentration of 0.5 wt% only. Therefore, RBW is used in the studies of oleogels in various food products such as sausage (Wolfer et al, 2018;Tarte et al, 2020), ice cream (Botega et al, 2013) and cookies (Zhao et al, 2020). The topic of oleogels is interesting only in the last decade.…”
Section: Organogelator In Oleogelsmentioning
confidence: 99%